Biological growth and synthetic fabrication of structurally colored materials. (11th June 2019) - McDougal, Anthony; Miller, Benjamin; Singh, Meera; Kolle, Mathias
Abstract: Nature's light manipulation strategies—in particular those at the origin of bright iridescent colors—have fascinated humans for centuries. In recent decades, insights into the fundamental concepts and physics underlying biological light-matter interactions have enabled a cascade of attempts to copy nature's optical strategies in synthetic structurally colored materials. However, despite rapid advances in bioinspired materials that emulate and exceed nature's light manipulation abilities, we tend to create these materials via methods that have little in common with the processes used by biology. In this review, we compare the processes that enable the formation of biological photonic structures with the procedures employed by scientists and engineers to fabricate biologically inspired photonic materials. This comparison allows us to reflect upon the broader strategies employed in synthetic processes and to identify biological strategies which, if incorporated into the human palette of fabrication approaches, could significantly advance our abilities to control material structure in three dimensions across all relevant length scales.